Tourism carrying capacity and environmental zoning of CEANA, oriented to visitors management and water resource protection in Cartago, Costa Rica - Castro-Barrantes, Leonardo (2020)
The Municipality of Cartago implemented by the end of the 2019 the Complejo Educativo Ambiental Naciente Arriaz (CEANA) as an innovative project oriented to environmental education for the community and aimed to become a model of sustainable practices that can be carried out to contribute to water protection. CEANA is located at a fragile ecosystem where water is collected from a spring and it is distributed to the surrounding population, so there is a need to generate information and management instruments aimed at its long-term conservation as well as look for the protection of its water resource. The objective of this research was to determine the tourism carrying capacity of its three visitor’s trails and establish the environmental zoning of the natural space. A forest inventory was carried out, it was performed a topographic survey on the three trails and high-resolution images of the area were taken with a drone. The maximum limit of daily visitors for Puente de Arco’s trail, Naciente Arriaz’s trail and Bosque en Regeneración’s trail were 31, 26 and 56 people, respectively. The environmental zoning of CEANA consisted of five management zones: low intervention zone, medium intervention zone, high intervention zone, natural regeneration zone and buffer zone.